(untitled) (Malaysian Management Journal, 2025)
This paper examines how working capital investment decisions relate to various internal and external risks faced by Malaysian firms. The study employed fixed effects instrumental variable estimation to analyse cross-sectional panel data from 406 firms listed on the Malaysian Securities Exchange (Bursa Malaysia). The results confirmed the hypothesised relationships between the various risks firms face and their working capital investment decisions. These relationships were statistically significant at the 5% or 1% levels for all risks, except for credit risk. Additionally, the connection between economic growth and a firm’s market strength in relation to its working capital investment was not confirmed. The industry analysis indicates that firms in the basic materials sector were more sensitive to all measured risks than firms in other sectors. This research fills a gap in the emerging economies literature by examining how working capital investment decisions relate to internal and external risks for Malaysian firms. The findings may assist firms in making more informed decisions regarding their working capital investments. To date, this is the first study to examine the impact of a broad range of risks on working capital investment decisions for firms in an emerging economy.